Penerapan metode game’s untuk meningkatkan keterampilan menulis dan karakter siswa pada mata pelajaran bahasa Indonesia - Delia Putri; Elvina Elvina (Universitas Ahmad Dahlan, 2019)
This study aims to improve writing skills using the impromptu game writer’s method. This type of research is action research. The research subjects were grade IV students at SD Negeri 006. The research instruments used were observation sheets and performance tests. The results showed that the character activity of students in the first cycle was in the sufficient category and the second cycle was in the good category. Furthermore, student learning outcomes in writing skills experienced a significant increase, namely pre-cycle with a class average of 62.76, cycle I with a class average of 68.71, and cycle II with a class average of 82.14. It was concluded that the method of the game's impromptu writers could improve writing and character skills in students.